Fundamentals of general pathomorphology - Хоперія, Вікторія Геннадіївна; Мостюк, Олена Михайлівна (Київський національний університет імені Тараса Шевченка, 2022)
The guide provides detailed syllabus descriptions of practical classes and theoretical material on the discipline Pathomorphology. The handbook is designed for postgraduate students of Health Care majoring in Medicine doing their Master of Medicine degree with a Doctor as a medical professional qualification.
Keywords: патоморфологія; охорона здоров’я